2011
DOI: 10.1152/ajpcell.00568.2009
|View full text |Cite
|
Sign up to set email alerts
|

VIP-dependent increase in F508del-CFTR membrane localization is mediated by PKCε

Abstract: The most common cystic fibrosis causing mutation F508del induces early degradation and reduced trafficking of cystic fibrosis transmembrane conductance regulator (CFTR) chloride channels to the apical membrane of epithelial cells. In the human nasal epithelial cells JME/CF15, we previously reported that vasoactive intestinal peptide (VIP) exposure corrects trafficking and membrane insertion of functional F508del-CFTR channels at 37°C. Correction of trafficking was PKA dependent, whereas enhanced membrane local… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 59 publications
1
9
0
Order By: Relevance
“…In Calu-3 cells, the most widely used model for human airway submucosal glands, stimulation of the G␣ s -PKA signaling cascade activates CFTR function by direct phosphorylation (21,22), whereas the G␣ q -PKC signaling pathway mainly regulates CFTR membrane density, also enhancing PKA-dependent activation by phosphorylation (11). In the present study, we first confirmed the role of PKCε in VIP-mediated increase in CFTR membrane density in Calu-3 cells with a specific inhibitor peptide, showing good correlation with our previous work on human airways and recombinant cells (1,11,46). Actin network and its associated proteins actively regulate the surface stability of many membrane proteins including CFTR (8,41).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In Calu-3 cells, the most widely used model for human airway submucosal glands, stimulation of the G␣ s -PKA signaling cascade activates CFTR function by direct phosphorylation (21,22), whereas the G␣ q -PKC signaling pathway mainly regulates CFTR membrane density, also enhancing PKA-dependent activation by phosphorylation (11). In the present study, we first confirmed the role of PKCε in VIP-mediated increase in CFTR membrane density in Calu-3 cells with a specific inhibitor peptide, showing good correlation with our previous work on human airways and recombinant cells (1,11,46). Actin network and its associated proteins actively regulate the surface stability of many membrane proteins including CFTR (8,41).…”
Section: Discussionsupporting
confidence: 90%
“…We previously reported that PKCε was involved in VIPdependent increase in F508del-CFTR membrane stability in the human nasal epithelial cells JME/CF15 (1,46). Here we used the cell-permeant PKCε inhibitor peptide EAVSLKPT to demonstrate the role of this isoform in VIP signaling cascade responsible for increase in CFTR membrane expression.…”
Section: Vip-dependent Increase In Cftr Membrane Localization Involvementioning
confidence: 93%
See 1 more Smart Citation
“…In human nasal epithelial cells (JME/CF15), derived from a F508del-CFTR homozygous patient, VIP treatment (300 nM) for 1 or 2 h induced the maturation and membrane insertion of functional F508del-CFTR proteins by stimulation of the VPAC1 receptor. Both the PKA and PKC⑀-dependent signaling cascade were found to be involved (1,30). The receptors are widely distributed in the body with some variation in cell type expressing VPAC1 and VPAC2 receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Cunha‐Reis et al () found that activation of VPAC1 receptors inhibited and activation of VPAC2 receptors increased gamma‐aminobutyric acid release, and both effects depend on the PKC mechanism. It has been reported that F508del‐cystic fibrosis trans‐membrane potential conductance regulator (CFTMP) membrane localization by VIP is mediated by PKC13ε (Alcolado et al, ). Our study suggests that both PKA and PKC pathways are involved in inhibiting the expression of IL‐17RC in fibroblasts.…”
Section: Discussionmentioning
confidence: 99%